2012
DOI: 10.2215/cjn.12761211
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxyvitamin D Response to Cholecalciferol Supplementation in Hemodialysis

Abstract: Summary Background and objectives Recent understanding of extrarenal production of calcitriol has led to the exploration of native vitamin D treatment in dialysis patients. This paper reports the pharmacokinetics of 25-hydroxyvitamin D response to 10,333 IU cholecalciferol given weekly in subjects on chronic dialysis. Design, setting, participants, & measurements This randomized, double-blind, placebo-controlled trial of 15 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
51
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 28 publications
10
51
0
4
Order By: Relevance
“…43 Potential harms with nutritional vitamin D supplementation include hypercalcemia, hyperphosphatemia, and extraskeletal ossification. In our study, in which 80% or more were concomitantly treated with VDRAs, there were no significant changes in calcium or phosphorus, and this is consistent with all of the other RCTs in patients on hemodialysis, 19,[22][23][24][25][26][27]31,[33][34][35] including one study that administered 200,000 IU of cholecalciferol weekly for 3 weeks. 27 Raising the possibility that there may be harmful outcomes associated with excess nutritional vitamin D administration, an RCT in community dwelling elderly women treated with a one-time dose of 500,000 units of ergocalciferol or placebo found a 15% increase in falls and a 26% increase in fractures in the ergocalciferol arm at 1 year.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…43 Potential harms with nutritional vitamin D supplementation include hypercalcemia, hyperphosphatemia, and extraskeletal ossification. In our study, in which 80% or more were concomitantly treated with VDRAs, there were no significant changes in calcium or phosphorus, and this is consistent with all of the other RCTs in patients on hemodialysis, 19,[22][23][24][25][26][27]31,[33][34][35] including one study that administered 200,000 IU of cholecalciferol weekly for 3 weeks. 27 Raising the possibility that there may be harmful outcomes associated with excess nutritional vitamin D administration, an RCT in community dwelling elderly women treated with a one-time dose of 500,000 units of ergocalciferol or placebo found a 15% increase in falls and a 26% increase in fractures in the ergocalciferol arm at 1 year.…”
Section: Discussionsupporting
confidence: 89%
“…There have been ten previous RCTs with sample size $30 patients and follow-up $8 weeks that have assessed the effects of nutritional vitamin D or calcifediol supplementation in patients on dialysis on iPTH, 19,[22][23][24][25][26][27]31,[33][34][35] and all but one small study 33 is consistent with the present study in finding no effect on iPTH. An absence of effect of nutritional vitamin D on iPTH has also been found in stage IV CKD, 36,37 while at earlier stages of CKD, there appears to be a reduction in iPTH with nutritional vitamin D. The conclusion from a Cochrane evidence review, published in 2009 before many of the above-mentioned trials were completed, concluded that vitamin D is effective in suppressing iPTH, although (not obvious from the abstract) this statement pertains to VDRAs and not to nutritional vitamin D. 38 The results of observational studies lead one to believe that there is a reduction in iPTH in patients on hemodialysis with nutritional vitamin D supplementation, 6,8,18,39 although these studies used historical controls and are limited by other biases inherent with a nonrandomized design.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the subgroup of cholecalciferol-treated patients for whom interim 25(OH)D levels were available, maximal levels were achieved by 8-12 weeks from commencement of therapy. This is consistent with another CKD-5D study, in which mean 25(OH)D levels of 30 ng/ml (75 nmol/L) were attained between 40 and 60 days from initiation of therapy (22). However, compared with this study, those patients had lower baseline 25(OH)D levels and were treated with lower cholecalciferol doses.…”
Section: Cholecalciferol Supplementation and 25(oh)d And 125(oh) 2 Dsupporting
confidence: 91%
“…A similar relationship of 25(OH) D to 1,25(OH) 2 D levels has been reported in anephric patients (23) and in a recent RCT of patients on dialysis (22). Whereas the former article supports the concept of extrarenal conversion of 25(OH)D to 1,25(OH) 2 D, the latter study and current trial cannot exclude the possibility of preserved or less inhibited 1-a-hydroxylase activity in vitamin D-supplemented patients.…”
Section: Cholecalciferol Supplementation and 25(oh)d And 125(oh) 2 Dsupporting
confidence: 81%